Indocyanine Green Near-Infrared Fluoroangiography Is a Useful Tool in Reducing the Risk of Anastomotic Leakage Following Left Colectomy - Neddermeyer, Miriam; Kanngießer, Veit; Maurer, Elisabeth; Bartsch, Detlef K. (Frontiers in Surgery, 2022)
Purpose: To evaluate whether visualisation of the colon perfusion with indocyanine green near-infrared fluoroangiography (ICG-NIFA) reduces the rate of anastomotic leakage (AL) after colorectal anastomosis. Methods: Patients who underwent elective left colectomy, including all procedures involving the sigmoid colon and the rectum with a colorectal or coloanal anastomosis, were retrospectively analysed regarding patients` demographics, operative details, and the rate of AL. Univariate and multivariate analysis was used to compare patients with and without ICG-NIFA-based evaluation. Results: Overall, our study included 132 colorectal resections (70 sigmoid and 62 LAR), of which 70 (53%) were performed with and 62 (47%) without ICG-NIFA. Patients‘ characteristics were similar between both groups. The majority of 91 (69%) procedures were performed by certified colorectal surgeons, while 41 (31%) operations were supervised teaching procedures. In the ICG-NIFA group, bowel perfusion could be visualized by fluorescence (dye) in all 70 cases, and no adverse effects related to the fluorescent dye were observed. Following ICG-NIFA, the transection line was changed in 9 (12.9%) cases. Overall, 10 (7.6%) patients developed an AL, 1 (1.4%) in the ICG-NIFA group, and 9 (14.5%) in the no-ICG-NIFA group (p=0.006). Multivariate analysis revealed ICG-NIFA as an independent factor to reduce AL. Conclusion: These results suggest that ICG-NIFA might be a valuable tool to reduce the rate of AL in sigmoid and rectal resections in an educational setting.